Alaskan Polar Bear Movements from Mark and Recovery - Lentfer, Jack W. (ARCTIC, 1983)
Alaskan polar bear mark and recovery studies from 1967-1976 and concurrent studies elsewhere indicate some interchange of polar bears between Alaska and the mainland coast of northwest Canada, but not between Alaska and the rest of Canada, Greenland, and Svalbard. The extent of movement between Alaska and the U.S.S.R. remains unknown. The number of Alaskan bears recovered in the same general area as marked suggests that the same animals tend to occur in the same general area in late winter and early spring each year. Distance traveled between marking and recovering sites and the proportion of animals that move to a different area are about the same for both sexes and for subadults and adults. Bears tend to disperse from commonly used areas in years when ringed seals are less available. The rate of movement in late winter and early spring is about the same for both sexes and for subadults and adults. After mid-April the predominant movement of bears north of Alaska is to the east.Key words: polar bear, Alaska, Arctic, mark-recovery, movement Mots clés: ours blanc, Alaska, Arctique, marquage-repérage, déplacement